Provisions on investment registration certificates upon establishment of enterprises and cooperatives in Vietnam – Shortcomings and recommendations for improvement - Cao Nhat Linh (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
An investment registration certificate in Vietnamese law is a written or electronic document that records the investor's registration information on the investment project. This Certificate is a mandatory prerequisite for foreign investors to establish or participate in establishing economic organisations in Vietnam, including companies and cooperatives. The methodology employed in this study is qualitative research. This study uses the literature approach and the Statute approach. This rule has a few exceptions, but it is usually required. Nevertheless, the Law on Investment, the Law on Enterprises, and the Law on Cooperatives all contain several illogical and inconsistent provisions for the most part. Because of this, the application of the law becomes more complex. Therefore, to enhance the Vietnam Law on Investment, it is essential to continue improving, revising, and supplementing the provisions of the Vietnam Law on Investment, the Vietnam Law on Enterprises, and the Vietnam Law on Cooperatives.